PENGAROH DISTILASI.FRAKSIONASI BUNGAKENANGA TEJU{ADAP BILANGAN ESTER DAN SIFAT MINYAKNYA - Bambang Wiyono; Abdul Hakim Lukman (Jurnal Penelitian Hasil Hutan, 1991)
The purpose of this research is to study the effect of fractional diatillation of cananga flower from Boyolalion the ester number and the oil properties. The properties were then evalw;ited based on the Ifido1U.1Bian Industrial Starrdard requirement for  cananga oil.  The fint  (ractiOn was obtained during the fint  0 -   6 houn  distilling time,  the second fraction was from 6 -   10 houn,  and third fraction '(rOm  11 -   15 hours."  .The raulta showed that the ester number of oil ('r(lctiom and the refractive index of the second and third fractions have met  with the 1ndonesian Industrial Standard requirement. The speci(ie gravity of oil fractions, hOwever, have not met  with  that standa~           'ester number of  the fint  fraction had  a higher value than that ot  the secorid fraction, and gradually lower value for• the third fraction. It  was found  from  this study- that the lint  fraction obtained from cananga oil distillation renders  the highest quality oil.